What to Say When Seeking Support Online: A Comparison Among Different Levels of Self-Disclosure - Pan, Wenjing; Feng, Bo; Wingate, V. Skye; Li, Siyue (Frontiers in Psychology, 2020)
The current study examined the effect of exposure to online support-seeking posts containing different levels of depth self-disclosure (baseline, peripheral) affected the quality (person-centeredness and politeness) of participants’ support-provision messages. Participants of the study were assigned to the role of a support-provider. Compared to participants who read support-seeking posts with baseline and core self-disclosure, participants who read support-seeking posts with peripheral self-disclosure rated the support-seekers as less anonymous. Compared to participants who read support-seeking posts in the baseline condition, participants who read the support-seeking posts with peripheral self-disclosure wrote support-provision messages with higher level of person-centeredness and politeness. Participants’ perceived anonymity of the support-seekers mediated the effect of the depth of self-disclosure on the politeness of the response messages.